Case Report: A testicular torsion as an initial presentation of a patient with metastatic cecum signet-ring cell cancer - Yu, Bo; Meng, Mi; Qin, Rui; Xu, Qiang; Zhang, Neng; Fu, Ni (Frontiers in Oncology, 2023)
Secondary neoplasms of the testes from solid tumors are rare and usually present as a painless mass. Metastatic cecum signet-ring cell cancer of the testis is extremely rare. The orchioncus usually shows hypervascularity on color Doppler ultrasound. The present study reports an unusual case of testicular secondary signet-ring cell carcinoma mimicking missed testicular torsion in a 55-year-old male patient with right scrotal swelling and intermittent pain for 10 days. As color Doppler ultrasound showed an avascular distribution of the enlarged right testis, missed testicular torsion was initially diagnosed. Right-sided orchiectomy was performed, and pathology of the resected testis revealed an intestinal-type adenocarcinoma with mucinous and signet-ring cell features. This pathological feature led to further endoscopic colorectal biopsy of the digestive tract, which revealed poorly differentiated adenocarcinoma of the cecum with signet ring cell features similar to those of testicular specimens. In conclusion, differential diagnosis should be considered for rare testicular neoplasms, as was seen in this rare occurrence of testicular torsion in a patient who initially presented with metastatic colorectal cancer. A correct preoperative diagnosis can change the management and outcome. This report shares our reasons for misdiagnosis and opinions on diagnosing and treating this kind of case.